A systematic review of person-centered approaches to investigating patterns of trauma exposure. (November 2017) - O'Donnell, Meaghan L.; Schaefer, Ingo; Varker, Tracey; Kartal, Dzenana; Forbes, David; Bryant, Richard A.A.; Silove, Derrick; Creamer, Mark; McFarlane, Alexander; Malhi, Gin; Felmingham, Kim; Van Hoof, Miranda; et al.
Abstract: Recent research has found that exposure to traumatic events may occur in certain patterns, rather than randomly. Person-centered analyses, and specifically latent class analysis, is becoming increasingly popular in examining patterns, or 'classes' of trauma exposure. This review aimed to identify whether there are consistent homogeneous subgroups of trauma-exposed individuals, and the relationship between these trauma classes and psychiatric diagnosis. A systematic review of the literature was completed using the databases EMBASE, MEDLINE (PubMed) and PsycINFO. From an initial yield of 189, 17 studies met inclusion criteria. All studies identified a group of individuals who had a higher likelihood of exposure to a wide range of traumas types, and this group consistently exhibited worse psychiatric outcomes than other groups. Studies differed in the nature of the other groups identified although there was often a class with high levels of sexual interpersonal trauma exposure, and a class with high levels of non-sexual interpersonal trauma. There was some evidence that risk for psychiatric disorder differed across these classes. Person-centered approaches to understanding the relationship between trauma exposure and mental health may offer ways to improve our understanding of the role trauma exposure plays in increasing vulnerability to psychiatric disorder. Highlights: Seventeen studies used latent class analysis to examine patterns of trauma exposure. Individuals group together across traumatic events to form reliable classes. There was some evidence that risk for psychiatric disorder differed across classes. These findings lead to more accurate models of vulnerability to psychiatric disorder.